2019
DOI: 10.1186/s13287-019-1165-5
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells: past, present, and future

Abstract: In recent years, stem cell therapy has become a very promising and advanced scientific research topic. The development of treatment methods has evoked great expectations. This paper is a review focused on the discovery of different stem cells and the potential therapies based on these cells. The genesis of stem cells is followed by laboratory steps of controlled stem cell culturing and derivation. Quality control and teratoma formation assays are important procedures in assessing the properties of the stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
893
0
30

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,270 publications
(927 citation statements)
references
References 194 publications
(139 reference statements)
4
893
0
30
Order By: Relevance
“…Studies have shown that oocyte health of heavy lactating dairy cattle is negatively affected contributing to the associated reproductive failure in the dairy cattle industry (Poirier et al, 2020). Also, oocyte reprogramming potential is crucial to the success of regenerative medicine (Zakrzewski et al, 2019). Hence, deeper understanding and research on oocyte development and its regulation is essential.…”
Section: The Making Of a Competent Oocyte -A Review Of Oocyte Developmentioning
confidence: 99%
“…Studies have shown that oocyte health of heavy lactating dairy cattle is negatively affected contributing to the associated reproductive failure in the dairy cattle industry (Poirier et al, 2020). Also, oocyte reprogramming potential is crucial to the success of regenerative medicine (Zakrzewski et al, 2019). Hence, deeper understanding and research on oocyte development and its regulation is essential.…”
Section: The Making Of a Competent Oocyte -A Review Of Oocyte Developmentioning
confidence: 99%
“…The differentiation ability of stem cells can be labeled with terms such as totipotent, pluripotent, and multipotent [17]. Totipotent stem cells can differentiate into any form of cells and even build organs.…”
Section: Differentiation Abilitymentioning
confidence: 99%
“…The plasticity of differentiation refers to the ability to differentiate into various types of cells, which is sometimes influenced by the surrounding tissue environment. Pluripotent embryonic stem cells and iPSCs are excellent in their ability to reproduce and differentiate into various tissues, while multipotent adult stem cells can have a limited ability of reproduction or differentiation compared to embryonic stem cells or iPSCs [17][18][19]…”
Section: Renewal and Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Adult stem cells can be obtained from various sources such as bone marrow, blood, fats and also readily available from gestational tissues such as umbilical cord, amnion and placenta. [1][2][3] Research on stem cells such as in vitro, using an animal as disease's model and also clinical trial to human is currently undergone for therapeutic purposes for many diseases. To date, most of the stem cells therapy is in the form of clinical research not commercially available yet for patients, unless for some indications with hematopoietic stem cells.…”
mentioning
confidence: 99%